Penerapan Model Intervensi BROSSING Pada Remaja Putri dalam Upaya Prevensi Generasi Stunting (Universitas Negeri Semarang, 2022)
Adolescent girls are the future mothers and their nutritional needs during adolescence is very important. Poor nutrition during adolescence can have negative effect, both the adolescents themselves and their descendants. Adolescent girls who experience anaemia and chronic energy deficiency will increase the risk of having low birth weight children (LBW). Infants with LBW have a higher risk of stunting than non-LBW infants. Lack of information about the nutritional needs of adolescent girls can be one of the factors that causes stunting problems in their descendants. The intervention effort that can be done is by conducting health education through a variety of media that appeal to adolescent girls. Health education in this activity used the media of education BROSSING (Bermain Monopoli Stop Stunting Itu Penting). BROSSING developed by a community service team to attract the interest of adolescent girls in understanding the importance of nutrition during the first 1000 days of life. The purpose of this community service activity was to build adolescent girls’ awareness on the importance of knowledge in nutritional needs during 1000 days of life. This activity was conducted gradually in SMA Negeri 18 Palembang. The activity started by reviewing the information needs related to nutrition in adolescent girls, then conducted health education which used lecture and simulation game methods with the media BROSSING. From this activity, the adolescent girls’ knowledge has increased and expected it can be the basis for forming healthy life behaviour in adolescent girls, especially in consuming nutritious and balanced food according to their needs.